2018
DOI: 10.15430/jcp.2018.23.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Located in the Upstream Region of the RPS19 Gene (rs2305809) Is Associated With Cervical Cancer: A Case-control Study

Abstract: Cervical cancer (CC) is caused by persistent human papillomavirus (HPV) infection and affects women worldwide. The progression of an HPV persistent infection to CC is influenced by genetic factors. Three single nucleotide polymorphisms (SNPs) in TP53, NQO1 and RPS19 genes (rs1042522, rs1800566, rs2305809, respectively) were previously associated with CC in European and North American populations. The present case-control study aimed to investigate the association of the SNPs rs1042522, rs1800566, and rs2305809… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As expected, proteins such as SOX2, POU5F1 (OCT4) (iPSC markers) and MAP2, DCX (neuronal markers) were enriched. Moreover, several proteins (e.g., INA, DPYSL4, and RPS19) were identified that have less established roles in the context of pluripotency and differentiation. Furthermore, a protein interaction network was visualized using Cytoscape, Genenmania plugin. Protein network analysis of these regulated proteins shows an interaction network around the proteins INA, NCAM, NEFM, and NEFL, being upregulated, and POU5F1, SOX2, DNMT3B, and DPPA4, being downregulated (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, proteins such as SOX2, POU5F1 (OCT4) (iPSC markers) and MAP2, DCX (neuronal markers) were enriched. Moreover, several proteins (e.g., INA, DPYSL4, and RPS19) were identified that have less established roles in the context of pluripotency and differentiation. Furthermore, a protein interaction network was visualized using Cytoscape, Genenmania plugin. Protein network analysis of these regulated proteins shows an interaction network around the proteins INA, NCAM, NEFM, and NEFL, being upregulated, and POU5F1, SOX2, DNMT3B, and DPPA4, being downregulated (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…RPS19 is a ribosomal protein, which can encode 40S subunit ribosomal protein. Studies have confirmed that it is significantly associated with cervical cancer and HPV infection [ 56 ]. In addition, RPS19 is significantly upregulated in prostate cancer, and it is believed to be a potential biomarker for prostate cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To identify differentially expressed proteins during neuronal differentiation in the two approaches, we compared T10 relative to T1 and performed a t-test for both neuronal subtypes separately. Figure 4A identified, that have less established roles in the context of pluripotency and differentiation [36][37][38]. The analysis of these regulated proteins shows an interaction network around the proteins INA, NCAM, NEFM and NEFL, being upregulated, and POU5F1, SOX2, DNMT3B and DPPA4, being downregulated ( Figure 4E).…”
Section: Proteomic Changes Across Time Points During Neuronal Differementioning
confidence: 98%